Penguatan Pengetahuan Ibu tentang Gizi Seimbang untuk Menjaga Imunitas Tubuh dalam Pencegahan Tuberkulosis: Strengthening Mothers' Knowledge of Balanced Nutrition to Support Immune Health during Tuberculosis Prevention - Ristanti, Ety Yuni; Asrar, Muhamad (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Nutrition is one of the most critical components influencing the immune system. Good nutrition prevents and accelerates recovery from infectious diseases, including tuberculosis. This community service project improves mothers’ knowledge of balanced nutrition to strengthen their immunity. The activities included training 30 homemakers in Dusun Bandari through lectures, discussions, and the distribution of informative booklets. Before the training, the participants completed a pretest questionnaire and material presentation, discussion, and post-test evaluation. The results indicated that most participants had limited knowledge before the training; however, after the training, most displayed a good understanding and could identify balanced, nutritious foods that enhance immunity to help prevent tuberculosis. In conclusion, conducting training or education on balanced and healthy foods is essential to encourage communities to apply such knowledge daily. This community service activity is expected to support government efforts in tuberculosis prevention by improving immunity through balanced nutrition.